2014
DOI: 10.1007/s10562-014-1389-z
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Prospects for Whole Cell Catalysis

Abstract: The ability of intact cells to perform chemical transformations has been periodically harnessed when technological, application, and market drivers have aligned. An example is the discovery of the therapeutic benefits of steroids and the realization that some cells could be used to perform selective oxidations that simplified existing multistep syntheses. The aim of the article is to provide some perspective on whole cell catalysis by first looking back at some approaches and successes such as steroid synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…For centuries, whole‐cell biotransformations have been used in the production of food and beverages. More recently, whole‐cell biocatalysis has become an active area of research due to its potential for low‐cost synthesis of fine chemicals, including chiral molecules and pharmaceuticals, natural food additives, and applications in bioremediation and energy . Whole‐cell biocatalysis benefits from complex multi‐enzyme reaction steps, applicability at ambient conditions, and attractive properties such as self‐repair and regeneration.…”
Section: Figurementioning
confidence: 99%
“…For centuries, whole‐cell biotransformations have been used in the production of food and beverages. More recently, whole‐cell biocatalysis has become an active area of research due to its potential for low‐cost synthesis of fine chemicals, including chiral molecules and pharmaceuticals, natural food additives, and applications in bioremediation and energy . Whole‐cell biocatalysis benefits from complex multi‐enzyme reaction steps, applicability at ambient conditions, and attractive properties such as self‐repair and regeneration.…”
Section: Figurementioning
confidence: 99%
“…Asymmetric reduction of prochiral ketone via biocatalysis is one of the most promising routes to prepare optically active alcohols. [1][2][3][4][5][6] Molecules with tetralone rings are used for the synthesis of many biological active and drug precursors. For example, Sertraline with a tetralone ring is used to treat disorder such as obsessive compulsive, post-traumatic stress, premenstrual dysphoric, and social anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalysts are increasingly used as efficient and environmentally safe alternatives than traditional catalysts in the production of fine chemicals, difficult to make using conventional organic catalysts. 4,[16][17][18][19] Mohammadi et al found that (S)-1-tetralol (S)-2 was obtained in 75% yield and 91% enantiomeric excess (ee) using Brassica oleracea whole-cell biocatalyst. 20 Similarly, Yadav et al reported that Daucus carota exhibited good performance in the asymmetric reduction of 1 to (S)-2 in terms of enantioselectivity (96% ee), but low conversion (70%) and yield (52%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies indicate that inclusion bodies produced by fusion of the target enzymes and the coiled-coil domain or aggregation-prone protein in Escherichia coli can retain some enzyme functions (Arié, Miot, Sassoon, & Betton, 2006;Diener, Kopka, Pohl, Jaeger, & Krauss, 2016;Jäger et al, 2018). Now, functional inclusion bodies begin to appear in biocatalysis (Domach, 2015;Kloss et al, 2018aKloss et al, , 2018b. For example, the activity of benzaldehyde lyase in functional inclusion bodies formed by using the domain 3HAMP (histidine kinases, adenylyl cyclases, methylaccepting chemotaxis proteins, and phosphatases) as fusion tags is three times higher than that of soluble enzyme for the synthesis of (R)benzoins (Kloss et al, 2018a).…”
mentioning
confidence: 99%